(untitled) (Global Scientific Review, 2026)
The current research aims to identify the impact of the Reciprocal Teaching Strategy on the development of inferential thinking among fifth-grade literary stream students in the subject of History. To achieve the research objective, the researcher adopted a quasi-experimental method due to its suitability for the research goals. The research population consisted of female fifth-grade literary students in public day intermediate and secondary schools affiliated with the General Directorate of Education in Diyala Province / Balad Ruz District. A school was randomly selected, and the choice fell on Al-Fadilat Secondary School for Girls. The sample consisted of 82 students, distributed across two sections: (A) and (B). Section (A) was randomly selected to represent the experimental group, which was taught using the Reciprocal Teaching Strategy, while Section (B) represented the control group, which was taught using the traditional method